Colon cancer exosome-derived biomimetic nanoplatform for curcumin-mediated sonodynamic therapy and calcium overload - Li, Yang; Huang, Chunyu; Xu, Youhua (Frontiers in Bioengineering and Biotechnology, 2022)
Sonodynamic therapy (SDT) possesses unique properties such as being minimally invasive, exhibiting low toxicity, as well as ability to impart the treatment in the deep tissues, and hence has been extensively used. However, inherent defects such as low water-soluble sonosensitizers can limit the clinical application of SDT, and tumor microenvironment (TME) can further compromise the effect of a single SDT. To overcome these challenges, we have designed a bionic nano-system (ECaC) by coating mesoporous calcium carbonate nanoparticles (CaCO3 NPs) and sonosensitizer curcumin (Cur) into tumor-derived exosomes for developing enhanced SDT. Exosome membrane could endow CaCO3 NPs with homologous targeting abilities. In addition, compared with the bare CaCO3 NPs, ECaC showed significant accumulation in the tumor cell species. Subsequently, CaCO3 NPs upon reaching the tumor site can be degraded into Ca2+ in response to the acidic microenvironment of the tumor to destroy the cellular mitochondria. Hence, the cellular respiration could be destroyed to be a vulnerable state, causing oxidative stress, enhancing Cur-mediated chemotherapy/SDT. This synergistically dynamic therapy has demonstrated significant anti-tumor effects under in vitro and in vivo settings without exhibiting any toxic side effects. Our prepared biomimetic nano-system can effectively deliver the hydrophobic Cur to the tumor sites, which holds great promise in field of drug delivery and can broaden the application of exosomes, as this method has a certain enlightenment effect on the subsequent development of exosomes.